THE INFLUENCE OF AUDITOR QUALITY, CORPORATE GOVERNANCE, AND TAX PLANNING ON PROFIT MANAGEMENT (Empirical Study of Manufacturing Companies on the Indonesia Stock Exchange) - Sumiati; Rico Nur Ilham; Chairil Akhyar; Darmawati (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
This study aims to analyze the Effect of Auditor Quality, Good Corporate Governance and Tax Planning on Earnings Management (Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange). The data analysis method used is panel data regression analysis and classical assumption test with the help of Eviews software. The sampling method used in this research is purposive sampling method. Partially, the results of the study state that audit quality and good corporate governance have a negative effect on earnings management in manufacturing companies on the Indonesia Stock Exchange. Tax planning has no effect on earnings management in manufacturing companies on the Indonesia Stock Exchange. Simultaneously audit quality, good corporate governance and tax planning affect earnings management in manufacturing companies on the Indonesia Stock Exchange.